PENGARUH MOTIVASI KERJA PRAMUGRAHA DALAM MEMBERSIHKAN KAMAR TAMU - Rejin Sakiaddat; Afriadi (Akademi Pariwisata Bunda Padang, Sumatera Barat, Indonesia, 2023)
This article aims to find out the work motivation of the room attendant's in cleaning guest rooms at Axana Hotel Padang. Motivation is a person's desire to do something due to encouragement from oneself or from outside oneself. In addition, motivation can also be interpreted as encouraging employees to take action because they want to do it. This study used a descriptive method, with data collection techniques through observation and dissemination of questionnaires with closed questionnaires. The results showed : (1) Career development from the company is not given to room attendants so that room attendants lack enthusiasm and tend to be emotional when the workload is too much, (2) Awards are supposed to be a motivation for room attendants but are not given at all by the company so that the same incident, that room attendants are not motivated to work, (3) The work motivation of room attendants is decreasing due to the very high workload and sometimes not in accordance with the established standards, causing complaints from guests which will have a negative impact on hotel revenue and hotel image to the community.